African Controversy: The Inheritance of the Donatist Schism in Vandal Africa - Whelan, Robin (The journal of ecclesiastical history, 2014)
A sense of an ending dominates accounts of African Christianity after the Vandal conquest of the 430s, not least as a result of the apparent disappearance of the Donatists in an Africa now ruled by Homoian Christians. In fact, the transfer from Donatist schism to new ‘Arian controversy’ more closely resembles the broader picture of Vandal Africa which has emerged from recent scholarship: significant continuity amid dynamic transformation. The cultural and rhetorical legacies of the Donatist schism were used by both parties (Catholic and Homoian) in Africa's new church conflict to present themselves as the true African Church.